2023
DOI: 10.1021/acs.jmedchem.3c01210
|View full text |Cite
|
Sign up to set email alerts
|

hIMB1636-MMAE, a Novel TROP2-Targeting Antibody-Drug Conjugate Exerting Potent Antitumor Efficacy in Pancreatic Cancer

Li-ping Sun,
Wei-qi Bai,
Dan-dan Zhou
et al.

Abstract: Herein, we first prepared a novel anti-TROP2 antibody-drug conjugate (ADC) hIMB1636-MMAE using hIMB1636 antibody chemically coupled to monomethyl auristatin E (MMAE) via a Valine–Citrulline linker and then reported its characteristics and antitumor activity. With a DAR of 3.92, it binds specifically to both recombinant antigen (K D ∼ 0.687 nM) and cancer cells and could be internalized by target cells and selectively kill them with IC50 values at nanomolar/subnanomolar levels by inducing apoptosis and G2/M pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…Previous work has suggested that TROP2 over-expression occurs in these cancer types [59]. Others have also recently reported preclinical evidence of tumor reduction using another TROP2-targeting ADC in xenograft mouse models of pancreatic cancer [60], consistent with our finding.…”
Section: Tacstd2 Case Studysupporting
confidence: 92%
“…Previous work has suggested that TROP2 over-expression occurs in these cancer types [59]. Others have also recently reported preclinical evidence of tumor reduction using another TROP2-targeting ADC in xenograft mouse models of pancreatic cancer [60], consistent with our finding.…”
Section: Tacstd2 Case Studysupporting
confidence: 92%
“…Considering that ADCs entered cancer cells by receptor-mediated endocytosis, maybe the limited Trop2 expression in MCF-7 cells restricted numbers of ADC molecules that entered the cells. While lidamycin demonstrated 100 times or more potent cell-killing activity than SN-38 in vitro, which might explain why hIMB1636-LDP-AE displayed more potent antitumor activity in MCF-7 xenograft model [47][48][49][50] . These results were consistent with the reports that the use of ADCs bearing more highly potent payloads would increase the probability of delivering a therapeutic dose to tumor cells with low antigen expression 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The promising in vivo antitumor effects are attributable to at least three MOAs: ADCC, the inhibition of cancer cell proliferation and migration, and the induction of cell cycle arrest and apoptosis. Sun et al further constructed an ADC version of hIMB1636 (hIMB1636-MMAE), using a Valine-Citrulline linker to conjugate mAb with three to four molecules of MMAE 64 . Not only does hIMB1636 retain the MOAs of its parent antibody, but it also achieves enhanced tumor inhibition via bystander effect in pancreatic cancer.…”
Section: Trop2-targeted Therapiesmentioning
confidence: 99%